The Health Toll of Import Competition - Jérôme Adda; Yarine Fawaz (Institute of Labor Economics (IZA), 2020)
This paper assesses the effect of import competition on the labor market and health outcomes of US workers. We first show that import shocks affect employment and income, but only in areas where jobs are more intense in routine tasks. Exploiting over 40 million individual observations on health and mortality, we find that import had a detrimental effect on physical and mental health that is concentrated in those areas and exhibits strong persistence. It decreased health care utilisation and increased hospitalisation for a large set of conditions, more difficult to treat. The mortality hazard of workers in manufacturing increased by up to 6 percent per billion dollar import increase.
Keywords: F16; I12; I18; 330; import competition; routine tasks; health; health behaviour; hospitalisation; mortality